Efektivitas Penegakan Hukum terhadap Residivis Tindak Pidana Narkotika: Studi Kasus Putusan Nomor 154/Pid.Sus/2018/PN Yyk dan Putusan Nomor 51/Pid.Sus/2020/PN Tte (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of recidivism in narcotics crimes indicates that the rehabilitation and punishment approaches applied have not been fully able to prevent recurrence of crimes. This study aims to analyze the effectiveness of law enforcement against recidivists in narcotics crimes in two court decisions, namely Decision Number 154/Pid.Sus/2018/PN Yyk and Decision Number 51/Pid.Sus/2020/PN Tte. Case studies are used to assess the effectiveness of law enforcement, especially against perpetrators who have previously undergone rehabilitation but have re-committed crimes with more complex roles. This study uses a normative legal method with a statutory approach and a case approach, which are analyzed qualitatively based on law enforcement theory and the objectives of punishment. The results show that normatively there are regulations on rehabilitation and increased sentences for recidivists, but their effectiveness is not optimal, partly due to the lack of post-rehabilitation regulations that are expressly regulated in the law and the lack of integrated data systems between rehabilitation institutions and the courts. This condition causes rehabilitation to not fully function as a preventive instrument against recurrence of crimes. This study recommends strengthening post-rehabilitation regulations and integrating information systems between agencies as part of a more preventive and sustainable criminal law policy reform.